SOME OBSERVATIONS ON THE INDEX OF CONDITION OF THE CLAM MERETRJX CASTA (CHEMNITZ) IN RELATION TO MUD AND WATER QUALITIES - Durve, V S; George, K V (Indian Journal of Fisheries, 2011)
The physiological condition (Index of condition) of Meretrix casta were studied in relation to pH, salinity, dissoloved oxygen, total and inorganic phosphates, silicates, nitrites and calcium, and varying coarseness of mud of the experimental ponds and the results ivere compared with similar observations on natural darn beds in the Athankarai estuary - 15 Km west of Mandapam Camp. The ponds with sandy muddy bottom and rich in nutrients do not seem to be suitable for the culture of this clam.